2009
DOI: 10.1016/j.ejvs.2008.12.009
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confirmation of the Role of Statins in Reducing Nitric Oxide and C-Reactive Protein Levels in Peripheral Arterial Disease

Abstract: Treatment with statins lowers plasma nitrite and CRP levels in patients with PAD. Our data support the effects of statins in vivo that have been demonstrated on the endothelium ex vivo, suggesting a beneficial effect by acting on the initial processes that trigger the disease, reducing oxidative stress (increase in the bioavailability of nitric oxide as peroxynitrite levels decrease) and curtailing the inflammatory processes which perpetuate the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Additionally, nearly all of the patients with dyslipidemia were being treated with statin medication, which may have improved their ambulation, inflammation, and oxidative stress measures. 2729 Finally, there are limitations associated with the design of the study. The correlations calculated between the clinical measures and the vascular biomarkers from this cross-sectional design do not allow causality to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, nearly all of the patients with dyslipidemia were being treated with statin medication, which may have improved their ambulation, inflammation, and oxidative stress measures. 2729 Finally, there are limitations associated with the design of the study. The correlations calculated between the clinical measures and the vascular biomarkers from this cross-sectional design do not allow causality to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that statins may reduce oxidative stress [ 47 ] by decreasing the generation of ROS, thereby synergizing with the biological effects of antioxidants [ 48 ]. The results of our study show that ceruloplasmin activity was influenced by both simvastatin therapy and surgical treatment, but only 7–10 days postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, statins prevent the oxidation of BH4 to BH3. The result of these processes is reduced oxidative stress in endothelial cells and improved eNOS function [43].…”
Section: Signaling Pathways and Molecules Mediating The Effect Of Stamentioning
confidence: 99%
“…A study which included 30 patients with peripheral arterial diseases showed that one-month of treatment with atorvastatin significantly reduced plasma ONOO− levels and reduced oxidative stress, resulting in reduced eNOS uncoupling and increased NO production [43]. Rasmusen et al also showed that atorvastatin combined with a NO precursor, arginine, exert anti-atherosclerotic actions via eNOS activation and NO production [82].…”
Section: Atherosclerosismentioning
confidence: 99%